Doctor Strange omnibus - Lee, Stan 1922-2018; Rico, Don 1917-1985; Thomas, Roy 1940-; O'Neil, Dennis 1939-2020; Ditko, Steve 1927-2018 (Marvel Worldwide, Inc, 2017)
A vain man driven by greed and hubris, Dr. Stephen Strange was a world-renowned surgeon until the night a car accident crippled his hands. Broken and destitute, he journeyed to Tibet to seek a cure from a legendary healer. He found not a man of medicine but the venerable Ancient One and the path to the mystic arts!
Keywords: Doctor Strange -- Fiktive Gestalt; Schwarze Magie; Superheld; Comic